PENGGUNAAN E-WALLET DALAM TRANSAKSI E-COMMERCE: ANALISIS UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY (UTAUT) - Puspaningrum, Rr Natasha Pramesthi Budi; Atahau, Apriani Dorkas Rambu (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
E-wallet is an electronic service used as a payment tool in electronic form where the amount of money will be stored in a certain electronic medium. However, there are still problems related to privacy and data security also network access while using e-wallet. The use of e-wallet is expected to increase efficiency and effectiveness in conducting transactions, helping the smoothness of small but frequent mass transactions. The Unified Theory of Acceptance and Use of Technology (UTAUT) analysis is used to predict a person's attitudes and acceptance of the technology used and provide information on what factors can encourage the user's attitudes. The purpose of this study is to analyze the use of e-wallets in transactions on e-commerce using the UTAUT framework and to determine the impact of using E-wallets as a non-cash payment tool for e-commerce using the Unified Theory of Acceptance and Use of Technology (UTAUT) framework on 109 student respondents of Faculty Economics and Business Satya Wacana Christian University using explanatory research through a quantitative approach. The results of this study prove that there are two accepted hypotheses. Only the social influence and facilitating conditions variables have a positive and significant effect on the user's interest in using the ShopeePay service with an interest in transactions on e-commerce.